The lesson : a novel - Turnbull, Cadwell, 1987- (Blackstone Publishing, 2019)
An alien ship rests over Water Island. For five years the people of the US Virgin Islands have lived with the Ynaa, a race of superadvanced aliens on a research mission they will not fully disclose. They are benevolent in many ways but meet any act of aggression with disproportional wrath. This has led to a strained relationship between the Ynaa and the local Virgin Islanders and a peace that cannot last. A year after the death of a young boy at the hands of an Ynaa, three families find themselves at the center of the inevitable conflict, witnesses and victims to events that will touch everyone and teach a terrible lesson.